Varieties of development paths in post communist countries with special regard to the transition in Hungary - Szanyi, Miklós (Competitio, 2012)
Transition in Central and Eastern Europe was carried out in various ways. However, the different countries’ current economic structure, institutions and main economic performance measures are rather similar. The question asked is whether these countries follow a specific kind of development model? What seems likely is that they differ substantially from CIS countries in many aspects. But they also seem to differ from existing models of capitalism more than they do from each-other. Based on this information, the varieties of capitalism literature assumes that such a model does indeed exist. However, no comprehensive positive description of the model has so far been provided. This paper tries to define the main elements of the CEE capitalist models. These are small open economies, with close integration into the world economy through foreign investments, a relatively limited and declining role of state redistribution, the problems of dual economic structure and insufficient job creation, a relatively large shadow economy and “business capture”-type cronyism. Further research is required to properly describe the elements and interactions among them.Journal of Economic Literature (JEL) classifications: D72, E65, P31